Izgradnja sistema socialnega skrbstva v Ljubljani po prvi svetovni vojni s poudarkom na delu socialnopolitičnega odseka in socialnopolitičnega urada - Šorn, Mojca (Prispevki za novejšo zgodovino, 2023)
The article, based on the materials of the Ljubljana Historical Archive, deals with the social welfare system in the Slovenian capital in the period between the two world wars. It presents its establishment and the wide range of plans and activities of the city's structures, while also focusing on periods of stagnation and their consequences. It is evident that the latter, under the impression of the mentality and attitude towards the socially deprived after the upheaval, could not stop the constant work and progress of the Ljubljana city offices in the field of social welfare between 1918-1941, and especially after 1923, when a network of regulated operations was established.
Keywords: 1918-1941; Ljubljana; socialno skrbstvo; socialnopolitični odsek; socialnopolitični urad